(untitled) (Alberta Journal of Educational Research, 2007)
This narrative study based on semistructured interviews seeks to further our understanding of students’ experiences of resilience factors and processes and of educators’ roles in engendering resilient environments. First, I provide a brief overview of current educational literature on resilience. Second, I draw on data from interviews with nine participants about their academic success in which they discuss personal resilience factors as well as resilience processes enacted in familial, friendship, and school environments. Last, I propose suggestions for further discussion and identify key issues for education administrators to be aware of in the creation and maintenance of school environments that foster resilience.